Pengembangan Mini Book Digital untuk Peminatan dan Perencanaan Individual Siswa SMA - Tiara Sari; Tri Umari; Dian Oktary (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Problems in interest and individual planning services at schools are often caused by social environmental pressure, mismatches between students’ interests and skills, and limited counseling service resources. This study aims to develop a digital mini book as a valid and practical supporting medium for guidance and counseling services. This study employed a Research and Development (R&D) method using the ADDIE model, although the development process was limited to the implementation stage. The research subjects consisted of material experts, media experts, and students as practicality assessors. Data were collected using validation sheets and practicality questionnaires and were analyzed descriptively using qualitative and quantitative approaches. The results showed that the digital mini book was categorized as highly valid, with a percentage of 96.6% from media experts and 87% from material experts. In addition, the practicality test conducted by students showed that the product was highly practical, with a percentage of 89.2%. Therefore, the developed digital mini book is considered feasible and practical as a supporting medium for interest and individual planning services. This medium can help school counselors provide information more practically and attractively through various counseling services, such as classical guidance, group guidance, and individual counseling.